Regulation of transepithelial transport of iron by hepcidin - NATALIA P MENA; ANDRÉS L ESPARZA; MARCO T NÚÑEZ (Biological Research, 2006)
Hepcidin (Hepc) is a 25 amino acid cationic peptide with broad antibacterial and antifungal actions. A likely role for Hepc in iron metabolism was suggested by the observation that mice having disruption of the gene encoding the transcription factor USF2 failed to produce Hepc mRNA and developed spontaneous visceral iron overload. Lately, Hepc has been considered the "stores regulator," a putative factor that signals the iron content of the body to intestinal cells. In this work, we characterized the effect of Hepc produced by hepatoma cells on iron absorption by intestinal cells. To that end, human Hepc cDNA was cloned and overexpressed in HepG2 cells and conditioned media from Hepc-overexpressing cells was used to study the effects of Hepc on intestinal Caco-2 cells grown in bicameral inserts. The results indicate that Hepc released by HepG2 inhibited apical iron uptake by Caco-2 cells, probably by inhibiting the expression of the apical transporter DMT1. These results support a model in which Hepc released by the liver negatively regulates the expression of transporter DMT1 in the enterocyte